Penerapan Hukuman Mati Tindak Pidana Korupsi di Indonesia Ditinjau dari Sisi Hak Asasi Manusia - Effendy, Andry; Magno, Nuno Gilherino Pacheco (Jurnal Hukum dan Demokrasi (JHD), 2024)
The rampant corruption that has plagued Indonesia recently has prompted law enforcement officials to continuously strive and brainstorm hard on how to impose punishments or sanctions that can deter corrupt individuals and those contemplating such despicable acts. Many suggestions and viewpoints have been put forth by observers and legal experts in the country regarding appropriate punishments for corrupt individuals to instill a sense of deterrence among wrongdoers and provide a "shock therapy" for those considering corrupt activities. Various actions have been proposed, such as imposing social sanctions, seizing all their assets (leading to poverty), and even imposing the death penalty on corrupt perpetrators. In the current era of reform, efforts to prevent and eradicate corruption and the corresponding punishments for offenders have evolved alongside the increasing discourse on imposing the death penalty for criminal acts. There are many arguments for and against the death penalty in corruption cases. These differing opinions on the death penalty vary, with some agreeing to set an example and serve as a deterrent to those considering similar actions, while others disagree because they find it unjust and a violation of someone's right to life. In Indonesia, the implementation of the death penalty for corrupt individuals is already regulated by laws and regulations. Article 2 paragraph (2) of Law No. 20 of 2001 regarding the Eradication of Corruption states: "In the event that the act of corruption as referred to in paragraph (1) is committed under certain circumstances, the death penalty may be imposed." Paragraph (1) reads as follows: "Any person who, unlawfully, enriches oneself or others or a corporation to the detriment of the state's finances and economy, shall be punished with life imprisonment or a minimum of 4 (four) years and a maximum of 20 (twenty) years of imprisonment and a fine ranging from at least Rp200,000,000.00 (two hundred million rupiah) to a maximum of Rp1,000,000,000.00 (one billion rupiah).